The Contribution of Sociology to Church Leadership: Promoting Social Justice and Unity in the Christian Community - Putrawan, Bobby Kurnia (MODERATE: Journal of Religious, Education, and Social, 2024)
This article explores the contribution of sociology to church leadership, particularly in promoting social justice and unity within the Christian community. Sociology plays a crucial role in understanding the social structures, relationships, and dynamics that exist within a church, and how these influence leadership practices. The purpose of this research is to examine how sociological principles can be applied to enhance church leadership, fostering an inclusive environment where justice and equality are central. The research employs a qualitative approach using library research, analyzing theological and sociological texts, with a specific focus on the role of sociology in leadership practices within the church. The findings show that sociology helps church leaders understand social interactions and group dynamics, enabling them to address social inequalities and promote unity within the congregation.   Contribution: This article contributes by highlighting the significant role of sociology in enhancing church leadership, particularly in fostering social justice and unity. It offers insights into how sociological principles can be applied to address social issues and improve relationships within the church community.